Implementasi Metode K-Means Clustering Dalam Pengelompokan Bibit Tanaman Kopi Arabika - Benny Ginting; Fristi Riandari (Politeknik Negeri Cilacap, 2020)
The emergence of various information on good coffee seeds to be planted has prompted the Agriculture and Plantation Service to group the seeds to be recommended in coffee planting centers in the working area of Sarimunthe Village, Kec. Munte Karo District. Data mining is used to extract valuable information from a dataset and then present it in a format that is easily understood by humans with the aim of making a decision. In this study, data processing for Arabica Coffee seedlings consisted of 30 items, in the Karo Regency Agriculture sector, in preparing the seeds to be distributed to the public, the assessment was divided into 3 phases, namely coffee seeds that did not produce (Phase 0-1 Year), immature (Phase 1-2 years) and produce (Phase 2 years and above). The final result of the grouping of Arabica coffee seedlings is that there are 10 recommended items suitable for planting